Recent trends in applying TPM to cloud computing - Shohreh Hosseinzadeh; Bernardo Sequeiros; Pedro R. M. Inácio; Ville Leppänen (Wiley, 2025)
Trusted platform modules (TPM) have become important safe‐guards against variety of software‐based attacks. By providing a limited set of cryptographic services through a well‐defined interface, separated from the software itself, TPM can serve as a root of trust and as a building block for higher‐level security measures. This article surveys the literature for applications of TPM in the cloud‐computing environment, with publication dates comprised between 2013 and 2018. It identifies the current trends and objectives of this technology in the cloud, and the type of threats that it mitigates. Toward the end, the main research gaps are pinpointed and discussed. Since integrity measurement is one of the main usages of TPM, special attention is paid to the assessment of run time phases and software layers it is applied to.